Effect of Glomus mosseae (Nicol. and Gerd.) Gerdemann and Trappe on root-knot disease of menthol mint (Mentha arvensis sub sp. haplocalyx Briquet) caused by Meloidogyne incognita (Kofoid and White) Chitwood - Akhtar Haseeb, K K Janardhanan, N Ratti, Abdul Khaliq, P K Shukla (Journal of Spices and Aromatic Crops, 2000)
Glasshouse experiments conducted to find out the effect of the vesicular-arbuscular mycorrhizal fungus, Glomus mosseae on reproduction of root-knot nematode Meloidogyne incognita and growth and yield of menthol mint (Mentha arvensis sub sp. haplocalyx) indicated that G. mosseae was effective in reducing populations of M. incognita and increasing growth and biomass productivity of menthol mint. Maximum supression in nematode populations was observed when G. mosseae was inoculated 15 days prior to inoculation of nematodes. Shoot length and oil yield of G. mosseae inoculated plants was significantly higher than uninoculated plants.